Strengthening Guarantees of Independence of Judicial Power Post Amendment to the 1945 Constitution - Andi Muhammad Asrun; Raden Muhammad Mihradi; Nazarudin Lathif; Mustika Mega Wijaya (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Amendments to the 1945 Constitution have provided even stronger guarantees for the independence of judicial power in Indonesia. The pre-amendment Constitution only mentions the promise of the freedom of judicial power in the Explanation section of the 1945 Constitution. The Explanatory Provisions have no binding legal force. The weakness of the law became a loophole for the interference of executive power in judicial power as occurred in the era of Sukarno (1959-1966) and the era of Suharto (1966-1998). In addition to strengthening the guarantee of judicial independence, amendments to the 1945 Constitution were also established by the Constitutional Court. The Constitutional Court exercises judicial power alongside the Supreme Court and the judicial bodies. Changes to the 1945 Constitution also assign duties to the Judicial Commission to supervise judges and judicial processes.